Prevalence and Determinants of Glycemic Abnormalities in Cardiac Surgery Patients without a History of Diabetes: A Prospective Study - Gianchandani, Roma Y.; Saberi, Sima; Patil, Preethi; Prager, Richard L.; Pop-Busui, Rodica (Frontiers in Endocrinology, 2015)
Objective To evaluate the prevalence and persistence of postoperative glycemic abnormalities in patients without a history of diabetes, undergoing cardiac surgery (CS). Methods Ninety-two patients without diabetes with planned elective CS procedures at a tertiary institution were evaluated preoperatively and 3 months postoperatively for measures of glucose control including hemoglobin A1c, fasting plasma glucose, 2-h post oral glucose load, and insulin levels. Data from the hospital course were recorded. Results Valid data were available from 61 participants at 3 months; 59% had prediabetes and 10% had diabetes preoperatively by one or more diagnostic criteria and continued to be dysglycemic at 3 months. Preoperative A1C was an independent predictor of postoperative hyperglycemia (p = 0.02). Insulin resistance and BMI rather than glycemic abnormalities before surgery were associated with a longer duration of the postoperative insulin infusion (p = 0.004, p = 0.048). Conclusion Seventy percent of CS patients without known diabetes met criteria for diabetes or prediabetes preoperatively, and these abnormalities persisted after surgery.